ANALISIS KESANTUNAN BERBAHASA MAHASISWA UNIVERSITAS BINA SARANA INFORMATIKA DALAM BERINTERAKSI DENGAN DOSEN MELALUI PESAN SINGKAT WHATSAPP: KAJIAN PRAGMATIK - Rd Bily Parancika; Erwin Setyawan (Universitas Muhammadiyah Lampung, 2020)
The more younger lecturers among young students, the more they would like to approach them, either during lecture or outside the class. The approach might make the relationship between lecturers and students closer and more emotional. However, it could seem less politeness which students have. This can be seen from the way and the language use through text messages on social medias, particularly on WhatsApp. This research aims to find out the variety of the students' politeness when having interaction with lecturers trough short message on WhatsApp by describing the students' language politeness, the principles of the deviation in politeness, the obedience and the function of the language politeness itself in the relationship between students and lecturers of Universitas Bina Sarana Informatika. Primary data in this research is written conversation records, especially screen shots of chats on WhatsApp. Secondary data is the knowledge of Pragmatic Studies of Bahasa Indonesia including the theories regarding language politeness principles in order to impact to the characters of the nation's next generation. The method used in this research is pragmatic studies, in particular with pragmatic and contextual equivalents.